Menembangkan Lontar Yusup Banyuwangi: Strategi Preservasi Warisan Budaya Lintas Generasi - Indiarti, Wiwin; Hasibin, Nur (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2018)
This article is based on the Community Partnership Program (PKM) which seeks to solve the problems facedby Osing indigenous community, especially the Mocoan Association of Lontar Yusup and The Archipelago IndigenousYouth Front (BPAN) of Osing from the aspect of preservation strategies and revitalization of the Mocoan Lontar Yusuptradition. The solutions offered from this program are the preparation of transliteration and translation of the contents ofLontar Yusup, digital documentation (pictures, writings, sounds and videos) stored in the form of Digital Video Disc(DVD) and Mocoan Lontar Yusup training for young people. The activities are in the form of making a book containingperso-arabic texts, transliteration and translation of the contents of Lontar Yusup, training module which contains theway to recite Lontar Yusup accompanied by digital documentation and Mocoan Lontar Yusup training for young peoplewhile the mentoring method was carried out by the team continuously during the period of the PKM program. Theoutputs are training modules, a book with perso-arabic texts, transliteration and translation of Lontar Yusup, digitaldocumentation, and the Mocoan Lontar Yusup training model for young people